The Anthropocene, hyperobjects and the archaeology of the future past - Campbell, Peter B. (Cambridge University Press, 2021)
Archaeology is often defined as the study of the past through material culture. As we enter the Anthropocene, however, the two parts of this definition increasingly diverge. In the Anthropocene the archaeological record ceases to be observed from a distance, but is something we exist within. It is not an assemblage of material culture, but a hyperobject of vast temporal and geographical scope, in which ecofacts increase in prominence and the role of artefacts recedes. This article examines the archaeological record as a hyperobject and argues for an expanded definition of archaeology for the future past. It argues for a shift from the study of objects towards a broader archaeology that includes immaterial Anthropocene culture.
Keywords: Anthropocene; object-oriented ontology; hyperobject; future